Fabrication and heat transfer characteristics of C/SiC pyramidal core lattice sandwich panel. (25th April 2015) - Wei, Kai; He, Rujie; Cheng, Xiangmeng; Pei, Yongmao; Zhang, Rubing; Fang, Daining
Abstract: Lightweight C/SiC pyramidal core lattice sandwich panel was proposed and fabricated for potential applications as hot structure and thermal protection system (TPS). The heat transfer characteristics of C/SiC lattice sandwich panel were measured from 600 to 1150 °C through an aerodynamic heating simulation experimental system. Temperature distribution on the back surface of the lattice sandwich panel was obtained through periodical thermocouple assignment. Heat insulation effects under different temperatures were also investigated. Finally, a three dimensional finite element simulation model was built to calculate the heat transfer of the C/SiC lattice sandwich panel. The equivalent thermal conductivity of the C/SiC lattice sandwich panel varied from 1.98 to 4.95 W/(m °C) when the front surface temperature increased from 600 to 1150 °C. It is believed that these results can provide a foundational understanding on the heat transfer characteristics of C/SiC lattice sandwich panel. Highlights: Lightweight C/SiC lattice panel was firstly proposed and fabricated. Heat transfer properties of the C/SiC lattice panel were tested up to 1150 °C. The heat insulation effect of C/SiC lattice panel achieved a peak value 90%. The equivalent conductivity of the C/SiC lattice panel increased with temperature.